2021
DOI: 10.1007/s11430-021-9819-y
|View full text |Cite
|
Sign up to set email alerts
|

Organic-rich formation and hydrocarbon enrichment of lacustrine shale strata: A case study of Chang 7 Member

Abstract: Lacustrine shale is an important target for the exploration of unconventional oil and gas in China beyond marine shale gas. However, the formation environment of lacustrine shale differs from that of marine shale, resulting in a different reservoir composition, organic matter, oil and gas content, and hydrocarbon mobility. In this study, the Chang 7 shale of the Yanchang Formation in the Ordos Basin was used to analyze the effect of volcanic activity on the paleoproductivity and preservation conditions during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 66 publications
0
19
0
Order By: Relevance
“…The black shales of the Chang 7 member in the Ordos Basin are generally characterized by a wide distribution area, large thickness, abundant organic matter, and suitable organic matter type and thermal maturity. Thus, it is regarded as the most significant oil and gas source for the entire Mesozoic oil reservoir [7,24]. The characteristics of source rocks vary in different regions due to the frequent changes in sedimentary facies in continental lacustrine basins.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The black shales of the Chang 7 member in the Ordos Basin are generally characterized by a wide distribution area, large thickness, abundant organic matter, and suitable organic matter type and thermal maturity. Thus, it is regarded as the most significant oil and gas source for the entire Mesozoic oil reservoir [7,24]. The characteristics of source rocks vary in different regions due to the frequent changes in sedimentary facies in continental lacustrine basins.…”
Section: Discussionmentioning
confidence: 99%
“…Recent shale oil exploration breakthroughs on the Bakken Formation of the Williston Basin, Eagle Ford Formation of South Texas, and Barnett Formation of the Fort Worth Basin in North America have reformed the energy structure of the United States and had a profound impact on the world energy pattern [2][3][4][5]. China also pay attention on shale oil and gas resources and made successively discovering in the Permian Lucaogou Formation of the Junggar Basin [6], the Triassic Yanchang Formation in the Ordos Basin [7], the Jurassic Ziliujing Formation in the Sichuan Basin [8], the Cretaceous Qingshankou Formation in the Songliao Basin [9], and the Paleogene Shahejie Formation in the Bohai Bay Basin [10].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, when the temperature is over 340 °C, the expelled oil GP continues to increase, whereas the residual oil GP first enters a stable plateau and then decreases rapidly. The petroleum expulsion efficiency is a key parameter to evaluate the conventional and unconventional oil and gas resources (Cooles et al, 1986;Pepper and Corvi, 1995;Ritter, 2003;Eseme, 2007;Eseme et al, 2012;Liu et al, 2022). Cooles et al (1986) defined the petroleum expulsion efficiency as a measure of the extent of expulsion from a given source rock section.…”
Section: Characteristics Of Oil Generation and Expulsionmentioning
confidence: 99%
“…Previous studies and stratigraphic sections revealed the presence of multiple volcanic ash interlayers in the Dalong Formation. Deep fluid activities such as volcanic activity can significantly promote the formation of organic-rich shale and the proliferation of hydrocarbon-forming organisms (Liu et al, 2019a;Liu et al, 2019b;Liu et al, 2022). However, for the Dalong Formation high-quality source rocks, further efforts are needed to clarify the relationship between types of hydrocarbon-generating materials and volcanic ash interlayers.…”
Section: Introductionmentioning
confidence: 99%